Higher Education and the Federal Budget - Musgrave, Richard A. (The Review of Economics and Statistics, 1960)
Richard A. Musgrave, Higher Education and the Federal Budget, The Review of Economics and Statistics, Vol. 42, No. 3, Part 2. Higher Education in the United States: The Economic Problems (Aug., 1960), pp. 96-101